THE IMPLEMENTATION OF LIFE SKILLS PROGRAMS IN ISLAMIC BOARDING SCHOOL BASED JUNIOR HIGH SCHOOLS IN TIGRAKASA TANGERANG REGENCY - Shinta Widiyanti; E. Nurzaman; Yulita Pujilestari; Sri Utaminingsih (Jurnal Manajemen Pendidikan, 2026)
This study examines the implementation of life skills programs in Islamic boarding school junior high schools (SMP) in the Tigaraksa area, Tangerang Regency. The research focuses on analyzing the processes of planning, implementation, and evaluation of life skills programs, as well as identifying supporting and inhibiting factors and the outcomes of program implementation in shaping students’ independence, character, and practical competencies. The integration of life skills education in boarding schools is considered a strategic effort to respond to the demands of the 21st century, which requires students not only to master academic knowledge but also to possess essential skills for real-life challenges. This research employed a qualitative descriptive approach using a case study design. The research subjects consisted of school principals, teachers, boarding school administrators, and students from several Islamic boarding school based junior high schools in Tigaraksa, including SMP Islam Al Mubarok, SMP Islam Nur Antika, and Pondok Pesantren Baitul Muqoddas. Data were collected through in-depth interviews, participatory observation, and documentation studies. The data analysis was conducted through stages of data reduction, data display, and conclusion drawing, supported by open coding, axial coding, and selective coding techniques. The validity of the data was ensured through source and technique triangulation